Three new species of Scythrididae from central Turkey (Lepidoptera: Scythrididae) - Junnilainen, Jari (Entomologica Fennica, 2002)
Three new species of Scythrididae are described, viz. Scythris alceella sp. n., S. lagomorphella sp. n. and S. tabelli sp. n., on the basis of material collected from the central Turkey, where they occur in open highland habitats. Another unknown species is described but left unnamed due to the paucity of material.